Angiotensin and Endothelin Receptor Structures With Implications for Signaling Regulation and Pharmacological Targeting - Speck, David; Kleinau, Gunnar; Szczepek, Michal; Kwiatkowski, Dennis; Catar, Rusan; Philippe, Aurélie; Scheerer, Patrick (Frontiers in Endocrinology, 2022)
In conjunction with the endothelin (ET) type A (ETAR) and type B (ETBR) receptors, angiotensin (AT) type 1 (AT1R) and type 2 (AT2R) receptors, are peptide-binding class A G-protein-coupled receptors (GPCRs) acting in a physiologically overlapping context. Angiotensin receptors (ATRs) are involved in regulating cell proliferation, as well as cardiovascular, renal, neurological, and endothelial functions. They are important therapeutic targets for several diseases or pathological conditions, such as hypertrophy, vascular inflammation, atherosclerosis, angiogenesis, and cancer. Endothelin receptors (ETRs) are expressed primarily in blood vessels, but also in the central nervous system or epithelial cells. They regulate blood pressure and cardiovascular homeostasis. Pathogenic conditions associated with ETR dysfunctions include cancer and pulmonary hypertension. While both receptor groups are activated by their respective peptide agonists, pathogenic autoantibodies (auto-Abs) can also activate the AT1R and ETAR accompanied by respective clinical conditions. To date, the exact mechanisms and differences in binding and receptor-activation mediated by auto-Abs as opposed to endogenous ligands are not well understood. Further, several questions regarding signaling regulation in these receptors remain open. In the last decade, several receptor structures in the apo- and ligand-bound states were determined with protein X-ray crystallography using conventional synchrotrons or X-ray Free-Electron Lasers (XFEL). These inactive and active complexes provide detailed information on ligand binding, signal induction or inhibition, as well as signal transduction, which is fundamental for understanding properties of different activity states. They are also supportive in the development of pharmacological strategies against dysfunctions at the receptors or in the associated signaling axis. Here, we summarize current structural information for the AT1R, AT2R, and ETBR to provide an improved molecular understanding.